Let's analyze Jacki's evaluation step-by-step to identify her error.
Jacki starts with the expression:
\[ 2^3 (3 - 1) + 4 (8 - 12) \]
-
She evaluates \( (3 - 1) \) and \( (8 - 12) \):
- \( (3 - 1) = 2 \)
- \( (8 - 12) = -4 \)
-
Now substituting these values back into the expression, we get: \[ 2^3 (2) + 4 (-4) \]
-
Next, she calculates \( 2^3 \):
- \( 2^3 = 8 \)
-
Substituting this value, we have: \[ 8 (2) + 4 (-4) \]
-
Perform the multiplications:
- \( 8 \times 2 = 16 \)
- \( 4 \times -4 = -16 \)
-
Now substituting these multiplications into the expression gives: \[ 16 - 16 = 0 \]
Jacki mistakenly calculated both the calculations from the subtraction operations as well as the final result.
The error in Jacki’s initial evaluation stemmed from incorrectly calculating \( 4 (8 - 12) \).
The correct evaluation should yield: \[ 2^3 (3 - 1) + 4 (8 - 12) = 16 + (-16) = 0 \]
So, the correct answer is: Jacki did not subtract 12 from 8 correctly.